Synthesis and characterization of segmented Polyurethanes based on Polyethylene and Polytetramethylene glycols part 2: thermo-mechanical and sweling properties. - Lan, Pham Ngoc; Hang, Nguyen Thu (VNU Journal of Science: Natural Sciences and Technology, 2004)
In the previous paper [1] we presented our study on the synthesis and characterization of some SPUs based on polyethylene and polytetramethylene glycols. Segmented polyurethanes (SPUs) are multiblock copolymers. Due to their specific phase separation characteristics caused by incompatibility between the hard and soft segments, they have quite good biocompatibility [2]. In this paper we present the second part of our study on the thermo-mechanicahand swelling properties of the SPUs based on polyethylene and polytetramethylene glycols. The effects of the macrodiols on the properties of the SPUs obtained were discussed.